2022
DOI: 10.3390/ijerph191610295
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Response Resource Allocation in Sparse Network Using Improved Particle Swarm Optimization

Abstract: Western China is a sparsely populated area with dispersed transportation infrastructure, making it challenging to meet people’s accessibility and mobility requirements. Rescue efficiency in sparse networks is severely hampered by the difficulty rescue teams have in getting to the scene of abrupt traffic accidents. This paper develops a layout optimization model for multiple rescue points to address this issue, suggests an improved particle swarm algorithm by including a variation that can reduce optimization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The heuristic optimization algorithm is widely used to solve problems in complex engineering projects [29][30][31][32][33][34], which can effectively solve nonlinear, multi-objective or multidecision variable optimization problems. The case of optimization design in the paper has many variables to be optimized (a total of 11 variables to be optimized), and the calculation model of the objective function is complicated (i.e., it's required to calculate the speed regulating characteristics in different working conditions of HMCVT for each individual in each iteration process of algorithm and consider the service time weight and efficiency of each HM stage in the whole life cycle of the tractor), so the research in the paper adopts the I-GA for the optimization design of transmission parameters.…”
Section: The New Hmcvt Optimization Design Methodsmentioning
confidence: 99%
“…The heuristic optimization algorithm is widely used to solve problems in complex engineering projects [29][30][31][32][33][34], which can effectively solve nonlinear, multi-objective or multidecision variable optimization problems. The case of optimization design in the paper has many variables to be optimized (a total of 11 variables to be optimized), and the calculation model of the objective function is complicated (i.e., it's required to calculate the speed regulating characteristics in different working conditions of HMCVT for each individual in each iteration process of algorithm and consider the service time weight and efficiency of each HM stage in the whole life cycle of the tractor), so the research in the paper adopts the I-GA for the optimization design of transmission parameters.…”
Section: The New Hmcvt Optimization Design Methodsmentioning
confidence: 99%
“…Some research can be found in railway [19] and air traffic management [20] fields. The related areas in road traffic management are, for example, the allocation of human resources in sustainable traffic management to obtain a day-to-day manpower allocation schedule [21], emergency response resource allocation [22], and the mathematical model for efficiency optimization by determining the best number of employees for an logistics task [23]. Those studies have a common point; the right number of employees affects the effectiveness of a system.…”
Section: Introductionmentioning
confidence: 99%